The men of Barbarossa : commanders of the German invasion of Russia, 1941 - Mitcham, Samuel W. (Casemate Publishers, 2009)
Arguably the largest military mission of all time, Operation Barbarossa changed the world forever. In this book we learn of the famous commanders and undersung leaders, casting a fresh perspective on one of history's most crucial campaigns.